Description of Work Related Neck Pain Among Employees in State Electricity Company (PLN Indonesia) - Mujiono, Mujiono; Udijono, Ari; Ma'rifati, Lu'luil; Dhista Rahmaningrum, Faikha (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: The use of electronic devices without proper usage techniques can result in a variety of health problems, including neck pain. This study aimed to describe neck pain problems among office workers who use electronic devices.Method: This study was quantitative research in which descriptive, observational, and cross-sectional methods were used. This study was conducted from July to December 2022 at the State Electricity Company at Semarang office, Indonesia. Total of 57 participants were chosen using a purposive sampling technique. A Google Form-based questionnaire was designed to collect the study data. Univariate analysis and cross-tabulation table were used.Result: Total of 60% of participants reported experiencing neck pain. The proportion of neck pain was higher among men and among older age (<35 years old). A more significant proportion of participants who reported neck pain were those who used their devices for ≥ four hours (94.4%) compared to users for < 4 hours. In addition, people with more than five years of employment length were more likely to report neck pain (75%) compared to employment with <5 years.Conclusion: This research concluded that work-related neck pain in the State Electricity company was due to improper use of electronic devices.